Effectiveness Test of Larvitrap Design of Plastic Jars with Type of Water on the Number of Aedes Sp Larvae Captured - Novitasari Agu Ate; Oktofianus Sila; Isnawati Isnawati (Poltekkes Kemenkes Kupang, 2025)
One of the safer methods of controlling dengue vectors is to break the life cycle of pre-adult Aedes aegypti mosquitoes (eggs and larvae) using larvitrap. The purpose of this study was to determine the effectiveness of larvitrap from black plastic jars based on the type of water that is effective against the number of trapped Aedes sp larvae. This study uses a “One shot case-study” design, which is a type of experimental research by observing under artificial conditions. The independent variables are larvitrap with well water and larvitrap with straw water, the dependent variable is the number of mosquito larvae trapped. The objects of the study were all Aedes sp. mosquitoes. Data analysis used a two-sample T test (t_test) using α (alpha) = 5%. The results of the study conducted by showing the effectiveness of larvitrap based on the type of water on the number of Aedes sp larvae showed that the average number of Aedes sp larvae trapped in the larvitrap with well water inside the house did not get aedes sp larvae and outside the house 7 tails/larvitrap. The average number of Aedes sp larvae trapped in the larvitrap with straw water inside the house was 22.3 tails/larvitrap and outside the house 30 tails/larvitrap. Based on the research results, it is recommended for the community to apply larvitrap to homes using plastic jars as a means of controlling mosquitoes that cause dengue fever